MO106A PROSPECTIVE STUDY ON ANXIETY AND BLOOD PRESSURE LEVELS IN HAEMODIALYSIS PATIENTS DURING COVID-19 PANDEMIC. (29th May 2021) - Eren Sadioğlu, Rezzan; Aktar, Merve; Duman, Berker; Kutlay, Sim; Sengul, Sule; Keven, Kenan; Nergizoglu, Gökhan; Ateş, Kenan; Ertürk, Şehsuvar
Abstract: Background and Aims: Coronavirus Disease-19 (COVID-19) pandemic has currently been one of the leading causes of psychosocial stress worldwide. We hypothesized that possible changes in anxiety status might affect blood pressure in haemodialysis (HD) patients during COVID-19 pandemic. Method: Seventy one prevalent HD patients were included in this prospective study. Hospital Anxiety and Depression Scale (HADS) and State-Trait Anxiety Inventory (STAI) were applied to assess psychological status of the patients. Peridialysis blood pressure measurements were performed and average of 6 consecutive HD sessions' pre-dialysis systolic blood pressure measurements were used for statistical analyses. All assessments were performed both at the beginning (March) and after ending (June) of the partial lock-down, which was officially instituted by the Government in parallel with the status of the pandemic in Turkey. Results: Mean age (±SD) was 59.2±14.8 years and 52% of the patients were female. Dose of medications including antihypertensives, dry weight, interdialytic weight gain, and Kt/Vurea were stable during the study period. STAI-state score was higher in March than that in June (44.6±12.6 vs 42.3±11.5, respectively, p=0.047), whereas HADS-anxiety, HADS-depression, and STAI-trait scores were not different. Pre-dialysis systolic blood pressure was significantly higher in March than in June (127.9±20.3 vs 124.8±22.8 mmHg, respectively, p=0.029). Change in state anxiety score from March to June was remarkable particularly in patients not taking a beta-blocker (49.3±9.6 to 43.8±11.1, p=0.001) and in patients younger than the median age of 64 years (48.6±12.8 to 45.3±12.5, p=0.029). Change in blood pressure level from March to June was found to be significant only in patients not taking a beta-blocker (123.4±20.2 to 118.2±20.6 mmHg, p<0.001), while did not reach a statistically significant level in the others. Conclusion: Our findings, though need to be confirmed by further studies, revealed an association between a higher state of anxiety and a higher blood pressure level in HD patients in COVID-19 pandemic era, which was remarkable particularly in patients not taking a beta-blocker.